Framing Media Online Kompas.com Terkait Isu Palestina Dan Israel - Yusuf, Raidah Intizar; Malik, Sahruddin; Hamson, Zulkarnain (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The purpose of this research is to evaluate the framing of the Palestine-Israel issue by Kompas.com where the framing will be analyzed using Robert Entman's framing analysis approach. A total of 27 news contents were analyzed from 7 May to 31 May 2021 in a cross-tabulation to analyze how Kompas.com defines problems, identifies causes, makes moral judgments, and recommends actions to solve these problems. The results of this study displayed in four schemes of Robert Entman's framing analysis, starting with 1) defining the problem, i.e. how Kompas describes the problems that occur, Kompas.com provides balanced information about events starting with evictions, which led to demonstrations, followed by the Jerusalem Day parade, which led to Israeli military repression; 2) diagnosis of causes, i.e how Kompas identifies what caused the problem to occur, and the presentation of Kompas.com is comprehensive enough to discuss the causes of each event; 3) make a moral assessment, i.e. how Kompas.com packs what is right and what is wrong in the events discussed, and uses words that are quite straightforward to blame Israel in the incident; 4) recommendations for treatment or recommendations for solutions from Kompas.com that put more pressure on Israel to stop violations of human rights